2019
DOI: 10.1002/mc.23005
|View full text |Cite
|
Sign up to set email alerts
|

Epimagnolin targeting on an active pocket of mammalian target of rapamycin suppressed cell transformation and colony growth of lung cancer cells

Abstract: Mammalian target of rapamycin (mTOR) has a pivotal role in carcinogenesis and cancer cell proliferation in diverse human cancers. In this study, we observed that epimagnolin, a natural compound abundantly found in Shin‐Yi, suppressed cell proliferation by inhibition of epidermal growth factor (EGF)‐induced G1/S cell‐cycle phase transition in JB6 Cl41 cells. Interestingly, epimagnolin suppressed EGF‐induced Akt phosphorylation strongly at Ser473 and weakly at Thr308 without alteration of phosphorylation of MAPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
5
1
Order By: Relevance
“…Moreover, aschantin did not inhibit protein kinase activities of PI3K, PDK-1, or AKT [11,12]. Recently, our research group reported that epimagnolin, a stereochemical epimer of magnolin, targets the active pocket of the mTOR kinase, but not that of ERK1 and ERK2, contrasting with our expectation that epimagnolin could inhibit the activity of ERK1 and ERK2 [13]. These results demonstrated that slight differences in chemical structure might produce large differences in the molecular targeting of proteins that are involved in human diseases including cancers.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…Moreover, aschantin did not inhibit protein kinase activities of PI3K, PDK-1, or AKT [11,12]. Recently, our research group reported that epimagnolin, a stereochemical epimer of magnolin, targets the active pocket of the mTOR kinase, but not that of ERK1 and ERK2, contrasting with our expectation that epimagnolin could inhibit the activity of ERK1 and ERK2 [13]. These results demonstrated that slight differences in chemical structure might produce large differences in the molecular targeting of proteins that are involved in human diseases including cancers.…”
Section: Discussioncontrasting
confidence: 86%
“…Additionally, we did not observe the cytotoxic effects of fargesin at 60 μM by 48 h in JB6 Cl41 cells (Supplemental Figure S2) as well as fargesin-induced apoptosis in JB6 Cl41 and HaCaT cells by 48 h and 72 h, respectively (Supplemental Figure S3). The cell cycle distribution of JB6 Cl41 and HaCaT cells in normal cell culture conditions was similar to the previous literature [11,13,22]. To examine whether the G1-phase cell cycle accumulation of JB6 Cl41 and HaCaT cells treated by fargesin was mediated by a growth factor-induced G1/S cell cycle transition or not, we starved the cells and co-treated them with EGF and fargesin as indicated.…”
Section: Fargesin-mediated G1/s Cell Cycle Transition Inhibition Suppsupporting
confidence: 78%
See 2 more Smart Citations
“…EGF Induces Cell Migration via MEK/ERK and PI3K/AKT Signalings, but Only p-AKT is Involved in the Wnt/b-Catenin Pathway ERK and PI3K/AKT are critical components of EGF-activated signaling, which has been associated with human cancer EMT (Wudtiwai et al, 2018;Jiang et al, 2019;Park et al, 2019;Yang et al, 2019;Yoo et al, 2019). To verify whether ERK and PI3K/ AKT could affect EGF-mediated migration of CAL27 cells, MEK inhibitor U0126 and PI3K/AKT inhibitor LY294002 were applied in observing the cell migration in the absence or presence of EGF (20 ng/mL) for 24 h. The results showed that pre-treatment with U0126 and LY294002 could reverse the EGFinduced migration (Figures 4A, B).…”
Section: Egf Regulates the Activation Of The Wnt7a/b-catenin Pathwaymentioning
confidence: 99%